2022
DOI: 10.1007/s00420-022-01923-y
|View full text |Cite
|
Sign up to set email alerts
|

Employment trajectories and mental health-related disability in Belgium

Abstract: Objectives An individual’s quality of employment over time has been highlighted as a potential determinant of mental health. With mental ill-health greatly contributing to work incapacities and disabilities in Belgium, the present study aims to explore whether mental health, as indicated by registered mental health-related disability, is structured along the lines of employment quality, whereby employment quality is assessed over time as part of individuals’ labour market trajectories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To better grasp the link between occupational downgrading and mental health in international migration, it useful to briefly refer to the substantial literature on the socioeconomic determinants of mental conditions ( Allen et al, 2014 ), among which occupational status features prominently ( Alegría et al, 2018 ). In the native population, unemployment and unfavorable work conditions have been consistently linked to mental and behavioral disorders ( Balogh et al, 2023 ; Barnay, 2016 ; Rönnblad et al, 2019 ). Research has also highlighted a negative association between mental health and psychological wellbeing on one hand, and over-education and skills underutilization on the other ( Bracke et al, 2013 ; Chen & Li, 2009 ; Dean & Wilson, 2009 ; Milner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To better grasp the link between occupational downgrading and mental health in international migration, it useful to briefly refer to the substantial literature on the socioeconomic determinants of mental conditions ( Allen et al, 2014 ), among which occupational status features prominently ( Alegría et al, 2018 ). In the native population, unemployment and unfavorable work conditions have been consistently linked to mental and behavioral disorders ( Balogh et al, 2023 ; Barnay, 2016 ; Rönnblad et al, 2019 ). Research has also highlighted a negative association between mental health and psychological wellbeing on one hand, and over-education and skills underutilization on the other ( Bracke et al, 2013 ; Chen & Li, 2009 ; Dean & Wilson, 2009 ; Milner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored whether vulnerability typologies differ in general health (Fujishiro et al 2021), mental health (Hasselhorn et al 2020;Keller et al 2017;van Aerden et al 2016), emotional exhaustion (Keller et al 2017), mental distress including stress, depression, and problems with emotions (Peckham et al 2019), emotional problems (Vanroelen et al 2010), and mental health disorders (Balogh et al 2023). Moreover, several studies showed that unfavourable working conditions are related to burnout (Shahidi et al 2021;Bouwhuis et al 2019), but without examining clusters of unfavourable working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there are some issues which will need to be addressed by research, such as RTW's definition, use of validated prognostic factors, disability in low-income countries, pathology-specific ICF Core-Sets (i.e., musculoskeletal disorders), and studies related to mental health (8) as it is associated with precarious and atypical forms of work (9) or exceptional events such as the pandemic.…”
mentioning
confidence: 99%